Land Subsidence Analysis of Reclaimed Land using Time-Lapse Microgravity Anomaly in Manado, Indonesia - Sandy Nur Eko Wibowo; Gybert E. Mamuaya; Rignolda Djamaluddin (Forum Geografi, 2018)
Coastal area land reclamation is a policy with various benefits, including its potential to increase economic growth. However, reclamation also potentially has adverse impacts on the environment, including increasing pressure on biodiversity, natural resources and natural ecosystems, and the most common problem is land subsidence. This study uses time-lapse microgravity anomaly to ascertain the distribution of gravity and vertical gradient anomaly in order to map the subsidence characteristics occurring in the Manado reclamation area. From the research that has been previously conducted, the positive gravity anomaly is spread around Megamall-Multimart to the north of Monaco Bay and on the southern side of Manado Town Square (Mantos). Positive anomaly values range from 3 to 29.7 μGal. The negative anomaly values are scattered around the Mantos and Megamas separating bridge and at some points around the Whiz Prime Hotel, Menora Church and towards the Pohon Kasih Megamas area. The reclaimed areas generally experience subsidence accompanied by a reduction in groundwater mass (Megamall and Mantos) due to the use of the groundwater by the community in these areas. Uplifts also occur at some points in the reclamation area of Megamas as a result of the occurrence of land subsidence. Longer-term research is needed to determine whether there is an increase in the rate of land subsidence in the Manado reclamation area. Over a longer period of time it can also be established whether there are other factors which affect land subsidence. Other geodetic methods to monitor subsidence, such as levelling, InSAR and GPS survey, which have been conducted in other locations, are also needed to obtain more detailed information about the land subsidence in this area.